Exploring creative development in professional youth football academies through an integrative transdisciplinary lens - Fardilha, F. (University of Stirling, 2021)
Creativity is the object of much interest in association football and is considered essential for successful performances. However, several high-profile coaches, players, and even scholars have argued that contemporary football lacks creativity. While the last three decades have been the most productive ever with regards to research on sporting creativity, little is still known about this complex, multidimensional construct. Furthermore, sporting creativity has been hitherto studied from a largely decontextualised, logical positivist paradigm, aimed at the identification and development of intra-individual traits and skills associated with creative performances. However, in recent years the field has witnessed a `sociocultural` turn that proposes a re-conceptualisation of creativity as a situated, distributed, and relational phenomenon. Departing from this perspective, the present thesis uses an integrative transdisciplinary approach to better understand the perceived decline in creative expression and development in contemporary association football, with a focus on professional football academies. These performance-oriented settings have singular characteristics (e.g. growing professionalisation and marketisation, high pressure, social closure, and hypermasculinity) that suggest they should be studied separately from participationoriented environments. Study 1 examines conceptualisations of creativity from Heads of Academy Coaching and Heads of Academy Recruitment across ten professional clubs and three different European countries (Portugal, Italy, England/Wales), comparing it with academic literature. Study 2 investigates the opportunities and challenges for developing creativity in a Portuguese professional football academy across multiple levels. Study 3 extends our knowledge regarding the development of creativity at the highest level of performance through a biographical case-study of `super-elite` player Bernardo Silva. In conclusion, I propose that more than a teaching/training process of natural abilities, creative development in football should be re-conceptualised as a broader, non-linear learning process, dependent on multiple interactions between a myriad of stakeholders - players, coaches, parents, teachers - across different formal and informal, socio-cultural and material environments.